(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2022)
In the present article, I review some evidence that shows how body odor disgust sensitivity (BODS) plays a central role in the so-called behavioral immune system (BIS), a set of processes aimed at detecting, emotionally reacting, and behaviorally avoiding pathogen threats. I also report empirical evidence on how the BODS relates to social attitudes such as authoritarianism, xenophobia, and condemnation of “impure” moral violations. This research is interpreted from an Evolutionary psychology framework